CFD Model of Turboprop Engine Nacelle Airflow for Ground Idle Condition - Goran Simeunović; Lukáš Popelka; Jaromír Fišer; Tomáš Vyhlídal; Petr Hatschbach (International Journal of Aerospace Engineering)
Research in this paper is concerned on bay cooling of the new type of turboprop engine. The considered engine integration substantially increases the temperature inside the front nacelle compartment. In order to achieve the optimal temperature conditions for engine parts inside the nacelle for all operating regimes and engine/nacelle regime after aircraft landing at heat soak-back, a new bay cooling system is proposed. Proposed cooling system consists of standard NACA inlets at the front of the nacelle, two additional groups of gills on rear part of front nacelle compartment, Zone1, and standard nacelle gaps (around exhausts), plus spinner gap. The sizing approach in the given multicriteria task is based on given temperature ratings of the engine accessories. Moreover, for structural reasons, metal skin and stiffeners in the front part of the nacelle should be maintained below the defined temperature limits. Using a 3D CFD model of the front nacelle compartment, this compartment is analysed, utilizing the software ANSYS. The benchmark testing of the considered turboprop engine of ATP type, performed by manufacturer, is used for defining the all necessary boundary conditions in this research.